Chicago’s South Side Free Clinic: A Medical Student-led Initiative and Community-Focused Effort to Re-engage Residents with Healthcare - Allen, Amani; Lang, Theodore; Fenton, David; Agwu, Chibueze; Acheampong, Kofi; Ayantoye, Idris; Oyola, Sonia; Peek, Monica E; Hampton, David (Journal of Student-Run Clinics, 2025)
Student-run free clinics (SRFCs) can provide primary care options for historically underserved communities. Chicago’s South Side is a predominantly African American community with poor access to medical care. Previously, SRFCs did not service this patient population. The South Side Free Clinic (SSFC) is a SRFC founded to establish sustainable health services directed by community organizations and stakeholders. University of Chicago Pritzker School of Medicine student leaders conducted a clinical needs assessment (CNA) identifying healthcare barriers. Through this com-munity-focused approach and an interdisciplinary partnership, the SSFC aimed to rebuild medical trust, to increase healthcare access, and to address health disparities. Between April-August 2022, 115 CNA responses were collected (South Side residents: 61% (70/115) versus non-South Side residents: 39% (45/115). Sixty-four percent (45/70) of South Side respondents stated they could afford their health insurance, however 72% (34/45) of respondents living outside of the South Side could not. The majority, 67% (77/115) of participants, reported that they would attend a SRFC. Since opening, the clinic has provided general medical check-ups, over-the-counter medications, point-of-care testing, routine access to primary care physicians, and preventive health services. Patient feedback, long-term surveillance, workflow efficacy tracking, and quality improvement metrics will help assess the South Side’s healthcare needs and identify future clinic service requirements. Ultimately, the SSFC will highlight and address the health care disparities impacting disadvantaged communities in Chicago’s South Side.